Research and Application of Induction Hardening Technology for Heavy Duty Gear Shafts - Rengui Shi; Ke Zhu; Weilin Zhang (Jixie chuandong)
The effects of induction quenching with different current frequency on the surface hardness， tooth root hardness， tooth core hardness， hardness gradient and metallography of gear shafts are analyzed and discussed by carburizing， tempering and induction quenching experiments of heavy-duty gear shafts. The results show that carburizing， quenching and tempering and induction quenching of 18Cr2Ni4WA steel gear shafts can effectively improve the surface hardness of the workpiece to more than 58 HRC， and improve the hardness gradient value of hardened layer. Improve the metallographic structure of hardened layer， and ensure the best hardness of the tooth core， so as to increase the bending fatigue strength of gear shafts. Therefore， a heat treatment method is provided for the low carbon alloy steel gear material containing more Cr， Ni， W and Mo after carburizing， which can improve the product quality.